2010
DOI: 10.12693/aphyspola.118.988
|View full text |Cite
|
Sign up to set email alerts
|

Structural Phase Transition in Liquid Crystal Doped with Gold Nanoparticles

Abstract: The influence of the inclusion of the dodecanethiol functionalized gold particles (with diameter 3-5 nm) on the structural transitions was investigated. The studied samples were based on the nematic liquid crystal 4-(trans-4 -n-hexylcyclohexyl)-isothiocyanatobenzene (6CHBT). The volume concentration of the gold particles was φ 1 = 2 × 10 −4 and φ 2 = 10 −3 . The obtained results showed that the inclusion of the gold particles in the 6CHBT liquid crystal increases the sensitivity of such system on the external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In particular, this results in a decrease of switching voltages and reduction of the switching times of LC displays (see, for example, refs. For example, a decrease of the N-I transition temperature is observed in nematics doped with approximately isotropic silver, [10] gold, [11] or aerosil particles, [12,13] while the N-I transition temperature increases if the nematic LC is doped with strongly anisotropic NPs including nanotubes, [14] magnetic nanorods, [15] and ferroelectric particles. Also, nematics doped with ferroelectric NPs are characterized by an enhanced dielectric and optical anisotropy, increased electro-optic response, [7,8] and improved photorefractive properties.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this results in a decrease of switching voltages and reduction of the switching times of LC displays (see, for example, refs. For example, a decrease of the N-I transition temperature is observed in nematics doped with approximately isotropic silver, [10] gold, [11] or aerosil particles, [12,13] while the N-I transition temperature increases if the nematic LC is doped with strongly anisotropic NPs including nanotubes, [14] magnetic nanorods, [15] and ferroelectric particles. Also, nematics doped with ferroelectric NPs are characterized by an enhanced dielectric and optical anisotropy, increased electro-optic response, [7,8] and improved photorefractive properties.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the nematic-isotropic (N-I) phase transition temperature is decreased when the nematic liquid crystal is doped with isotropic silver [14], gold [15] or aerosil [16,17] NPs . At the same time, doping with strongly anisotropic NPs leads to an increase of the N-I transition temperature, which has been observed using nanotubes [18], magnetic nanorods (NRs) [19], and ferroelectric NPs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been experimentally shown that the nematic-isotropic (N-I) phase transition temperature can be affected by the presence of various NPs. For example, a decrease of the N-I transition temperature is observed when the nematic phase is doped with isotropic silver [11], gold [12] or aerosil particles [13,14], while the N-I transition temperature increases if the nematic LC is doped with strongly anisotropic NPs including nanotubes [15], magnetic nanorods [16] and ferroelectric particles [17,18]. Recently a molecular-field theory of nematic LCs doped with both isotropic and anisotropic NPs has been developed [19] which enables one to describe the shift of the transition temperature and the effect of the orientational order of the anisotropic NPs on the nematic order of the host phase.…”
Section: Introductionmentioning
confidence: 99%